(3VhA GdUHM GdeSaQ hLfi GdOhM GdeKeQs - (3CMeO Hf Ydj Hf CMeO GdaRGQj GdbGgQj GdbdbTfOj , TgGH GdOjf, CHh GdYHGS, J (B821 (3g` s
(3ChdgG (B:s
(3GdMeO ddg LGYd VhA GdUHM YRg fgGQg adeG cGf cJGHi UHM GdGYTi ai cJGHI GdGfTG s
(3BNQgG (B:s
(3hGJe hRGO Gddg edcce hSdWGfce hGdSdGe Ydi LdSGFce s
(3HgG fXGe GdJYbjHIs
(3fSNI NRGFfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B317s
Keywords: (3GdCOHs